The Role of Nurses in Fetal Cardiology Programs: An Integrative Review. Issue 3 (May 2023) - Butler, Mary; McArthur, Erin C.
Abstract: Background: Fetal cardiology programs are evolving quickly and include multiple interdisciplinary health care professionals whose roles could benefit from clear definition. Nurses provide an essential function in this field; however, descriptions or definitions of nursing practice, education and knowledge requirements, and responsibilities are limited and vary across institutions and disciplines. Purpose: To conduct an integrative review summarizing the literature to determine the role of nurses in fetal cardiology programs. Methods: We conducted an integrative review as per Whittemore and Knafl's (2005) methodology of current literature to reveal strengths and opportunities in describing nursing practice as fetal cardiology nurses. The search strategy included five electronic databases: CINAHL, Medline, PsycINFO, Web of Science, and Google Scholar. Peer-reviewed English-language articles discussing nursing practices in fetal cardiology published between 2015 and 2022 were selected. Data extraction and analysis were completed on a final sample of 26 articles. Results: Four themes were identified on fetal cardiac nursing practice from nursing and medical perspectives: multidisciplinary key team member, psychosocial family support and counselor, coordinator or navigator, and role description. Clinical Implications: More discussion in the literature is needed to better understand and define fetal cardiac nursing practice. Although most experts agree nurses are an important member of the interdisciplinary fetal cardiology team, their roles and educational requirements are poorly described and defined. Quality metrics and benchmarks are needed to ensure safe and effective fetal cardiology care. Abstract : The role of nurses in fetal cardiology programs is not fully described in the literature. Nursing practice and requirements for knowledge, skills, and education vary among programs and countries. In this integrative review of 26 articles from 9 countries, the role of nurses in fetal cardiology programs is explored and recommendations for role definition, quality measures, and educational requirements are discussed.